Association between hair cortisol levels and keratoconus: A prospective study - Noor Alqudah; Nosayba Al-Azzam; Leen El Taani; Mohammad Al Qudah; Abdallah Sharayah; Rita A. Al-Rihani (PLoS ONE, 2025)
Introduction Keratoconus is a progressive corneal disorder characterized by corneal thinning often leading to significant visual impairment. Recent research suggests a potential role of cortisol in the development and progression of keratoconus. However, the relationship between cortisol levels and keratoconus severity remains poorly understood. Purpose To investigate the association between hair cortisol levels and keratoconus severity in a Jordanian population, exploring whether cortisol could serve as a potential biomarker for disease progression or stability. Methods We conducted a prospective, observational study at King Abdullah University Hospital in Jordan. Sixty participants aged 18–30 years were categorized into three groups: Healthy (n = 20), Progressive Keratoconus (n = 20), and Stable Keratoconus (n = 20). Demographic, clinical, and ocular data were collected, including age, gender, hair cortisol levels, and corneal topography indices (Kmax, Kmean, and thinnest corneal location). Results The median cortisol level was significantly higher in the Progressive Keratoconus group (987 pg/mL) compared to the Stable group (300 pg/mL, p-value <0.001). Regression analysis revealed a significant negative association between cortisol levels and stable keratoconus (β = −1.31, p < 0.001). No significant association was observed for progressive keratoconus after adjustment for age and gender. Correlation analysis showed no significant associations between cortisol levels and BMI, Kmax, or Kmean. Cortisol levels also did not vary significantly across keratoconus severity categories in either eye. Conclusion Elevated cortisol levels may be associated with keratoconus progression, while lower levels appear linked to disease stability. Cortisol could serve as a potential biomarker for disease monitoring; however, further multicenter studies are needed to validate these findings and clarify cortisol’s role in keratoconus pathogenesis.